A study on the choice of library for career practice by U.P. Bachelor of Library Science graduates from school year 1993-1995 - Lucero, Dante Winston S.; Buenrostro, Juan Jr. C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1997)
This thesis aims to study the factors which influenced the Bachelor of Library Science graduates of the University of the Philippines Institute of Library Science for the school years 1993, 1994, and 1995 in their decision to transfer to another type of library in practicing their careers in librarianship. The objectives of the study are to find out what type of library the UP BLS graduates are working at present, why they chose such type of library for their career practice; to determine how many libraries have they worked before and what type of libraries were they; and to
This study used the descriptive survey research method using a questionnaire as a tool for gathering data. The subjects of the study are 28 Bachelor of Library Science graduates of the UP Institute of Library Science for the school years 1993, 1994, and 1995.Findings of the study showed that there are more female than male graduates who are practicing librarianship. Most of the respondents belong to the 24 years old bracket with most of them completing their secondary education from the National Capital Region. The educational attainment of the parents is not an influencing factor for the choice of librarianship as a profession by the respondents. The following are the reasons why most of the respondents chose the type of library they are connected with at present: 1) opportunity for career growth and training; 2) specialized collection; 3) work place is near home; 4) broad coverage of the collection; and 5) library is easy to manage and maintain. Most of the respondents have no plans of transferring to another type of library due to the following reasons: a) familiarity with the collection and users; b) new adjustment in transferring again; c) satisfaction with the present library; and d) the choice of doing more research than library work. If ever they will transfer, competitive compensation/high salary and job description/responsibilities as a librarian are the two main considerations.
Vita.
Computer print out.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Vocational guidance -- Philippines -- Quezon City; Library science; University of the Philippines. Institute of Library Science -- Graduate students